Thông tin Khoa học (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Call for Papers: International Conference Invitation (Psychological Trauma and Support Activities)It is to the great honor of The Faculty of Psychology, University of Social Sciences and Humanities, Vietnam National University in Hanoi and The Mental Health Institute, Bach Mai Hospital to invite you to participate in The 1st International Conference on “Psychological trauma and support activities”.• Context and conference objectives1.1. ContextSince the last decades, scientists all over the world have been trying to understand the nature, and consequences of psychological trauma and its support methods. The study of psychological trauma is always placed in the relationship between biological, psychological and environmental factors.Nowadays, people's lifestyle is faster paced; human relationship, even among family members, becomes more distant, and people, young and old, suffer more pressure. Besides, the values differences ​​and conflicts of interests among individuals, groups, religions, communities, and ethnic groups become more acute in the context of globalization. These issues contribute to an increase of trauma in people, both physically and mentally.In Vietnam today, despite the fact that psychological trauma has gathered more concerns, psychological support activities have only been implemented in small-scale and not at a professional level. People engaged in psychological support have not been professionally trained. Scientific bases and specific professional code on support contents, methods, processes are lacking and do not really match the reality. In particular, supervision activities are virtually absent.Therefore, the organization of the scientific conference "Psychological trauma and support activities", which aims at connecting scientists, sharing knowledge and experience in training and practice of intervention, treatment, and supervision, is necessary and of critical significance.1.2. Conference objectivesThe workshop focused on discussing the problems of theory and practice of psychological trauma and support activities to develop support programs and effective interventions in the current context of globalization.• ContentThe conference focuses on 4 main issues:2.1. Theory, methodology, intervention, and assessment: Theories of psychological trauma; approaches in assessment, supervision and intervention; research and support methods.2.2. Psychological trauma in children and adolescent: In the case of being subjects of bullying, violence or abuse; injury; stigmatization, discrimination; addiction (drugs addiction, gaming, social networking,...); abandonment, being orphaned, and lack of parental care.2.3. Psychological trauma in adults: Due to stress at work, unemployment, work related accidents, traffic accidents; domestic violence; pregnancy and childbirth; midlife crisis; and psychological problems in the elderly (retirement, solitude, preparing for death).2.4. Culture, social groups and psychological trauma: Culture integration, acculturation and psychological trauma; vulnerable groups (homosexuals, people with HIV, drug users, etc.); immigrants and refugees; majority and minority groups; terrorism, war and natural disasters.• Languages spoken in the Conference: Vietnamese, English, French• Hold time: 7th-8th November 2016• Venue: University of Social Sciences and Humanities, 336 Nguyen Trai Street, Hanoi, Vietnam• Article normArticles must range from 5,000 to 10,000 words (about 10-15 A4 pages), in Unicode font (Times New Roman), font size 12, 1.2 line spacing. Abstracts must be within about 200 to 300 words in length (Vietnamese and English / French). Articles should be well-structured and adequately cited to scientific standards, and keywords are clearly mentioned. The articles will be peer-reviewed and selected for publishing in the Proceedings of the Conference (Vietnam National University in Hanoi Publisher, ISBN).• Deadline for Submission- Abstract: until 30th May 2016- Full text: until 30th July 2016Send to:Bui Thi Hong Thai, Ph.D:Email: buihongthai2003@yahoo.comNguyen Van Luot, Ph.D:Email: nguyenvanluot@gmail.com.For more information, please contact:(1). Nguyen Van Luot, Ph.D., Faculty of Psychology, University of Social Sciences and Humanities, 336 Nguyen Trai street, Thanh Xuan district, Hanoi, Vietnam ;Phone (+84)912229910; E-mail: nguyenvanluot@gmail.com.(2). Dang Thanh Tung, MA.Mental Health Institute, Bach Mai Hospital;Phone (+84)904103009E-mail: tungdangthanh@bachmai.edu.vn Nguyen Van Luot Call for papers: Cultural Resources for Sustainable Development: Theories, Practices and Policy Solutions Organized by VNU Hanoi College of Social Sciences and Humanities in collaboration with Vietnam Association of Ethnology and Anthropology, VASS Institute of Cultural Studies, VASS Institute of Cultural Studies, Museum of Nguyen Van Huyen 15 and 16 December 2016, Hanoi, VIETNAM  • BackgroundIn the past quarter of century, cultural resources and the role of culture in sustainable development at both global and local levels have been increasingly recognised by researchers and policy-makers. It has been suggested that policies and development projects in various areas can yield more sustainable outcomes when more attention is paid to cultural resources. However, research and applied work in this field still face challenges. One important reason is the complex and multi-dimensional relationship between cultural resources and sustainable development, to which there have been different analytical approaches. Meanwhile, in practice, top-down approaches often make the incorporation of cultural resources into policies and development projects a challenging task.After 30 years of đổi mới, regional and international integration, Vietnam has achieved outstanding achievements in economic sector, foreign relations and political stability. However, the Party, the state in Vietnam, along with many researchers, have recognised such socio-economic developments not yet sustainable. They recognize the need for a holistic development strategy and innovative projects in order to build a society that achieves a better balance among economic development, environment quality and social equity through the incorporation of cultural resources. Various suggestions have been made that such development objectives can be achieved through a better and more systematic identification of cultural resources and their incorporation into sustainable development at both macro and micro levels.• AimsIn such a context, with a holistic approach and on the basis of their academic and applied research, anthropologists and other researchers need to have a stronger voice and more efficient contribution to the question of how cultural resources can contribute to sustainable development at different levels and in different localities.    This international workshop will be a forum for participants from Vietnam and other countries to share research findings and their theoretical and practical implications, to discuss policy solutions and to suggest applied models for cultural resource identification, preservation, and incorporation for sustainable development.The workshop aims to address and illuminate some of the following questions:- How and in what ways can cultural resources contribute to sustainable development?- What is the present situation of cultural resources for sustainable development in different countries?- What are the better approaches and tools for identifying, conserving and utilizing cultural resources for sustainable development?- What are policy solutions and models for incorporating cultural resources in sustainable development?- What can we do to enhance and strengthen research and teaching on cultural issues and sustainable development in Vietnamese universities, and to contribute to the country’s sustainable development process and the implementation of Sustainable Development Goals. • Themes- We would like to ask each paper to cover and address one or more of the following themes:- Culture and sustainable development: History, theories and methods.- Cultural heritage for sustainable development.- Customary laws, beliefs, festivals, local knowledge, and other traditional institutions/practices in sustainable development.- Cultural tourism and sustainable development.- Cultural policy in sustainable development- Policy solutions, models for incorporating cultural resources in sustainable development.• FormatThe workshop will be held over one day and a half, including plenary sessions and thematic sessions. Simultaneous interpretation will be offered in English and Vietnamese.• Submission guidelines and workshop contact addressPaper abstracts should be between 250 and 300 words and full papers should be no more than 10,000 words and should be sent to Assoc. Prof. Nguyen Van Suu: nvsuuvnu@gmail.com- Important dates:+ 20/3/2016: First announcement+ 30/6/2016: Deadline for abstracts+ 10/7/2016: Second announcement+ 21/11/2016: Deadline for papers+ 30/11/2016: Third announcement+ 15-16/12/2016: Conference- Workshop contact address:Assoc. Prof Nguyen Van Suu.Email: nvsuuvnu@gmail.com Nguyen Van Suu From Cambridge to Vietnam: Teaching and learning Anthropology in today’s global worldAs part of the regular series of seminars organized by Faculty of Anthropology, on April 12th, 2016, Prof. Susan Bayly from Cambridge University (United Kingdom) delivered a speech entitled “From Cambridge to Vietnam: Teaching and learning Anthropology in today’s global world”. In the first part of her presentation, Prof. Susan Bayly shared her experiences in teaching and researching Anthropology at Cambridge University; the shifting approaches to Anthropology in the world, from emphasizing macro issues such as social structures or systems to focusing on human’s experiences, the voice of the researched community, and the close ties between field research and theory as they are two indispensable parts of Anthropological studies. In the next part, Prof. Susan Bayly shared her personal experiences after more than 15 years working in Vietnam, especially her interest in a range of interesting topics in contemporary Vietnam, such as the experiences of intellectual families in Hanoi since the August revolution and the social conception of “achievement” in Vietnam nowadays. Prof Bayly especially highlighted the importance of the life-long cooperation between her and the Faculty of Anthropology at Cambridge University and the USSH’s Division of Ethnology back then and Faculty of Anthropology today. In her opinion, although the two countries’ traditions of Anthropology somewhat differ in their approaches, they share a common theme, which is the belief in Anthropology as a distinct discipline that is particularly relevant to human’s experiences and the ways human adapts to an ever-changing world, which are always viewed with a sympathetic, respectful and understanding sentiment.In the Q&A session, Prof. Susan Bayly openly shared her opinions with the scholars and students that were listening on various issues such as the role of anthropologists in devising policies and advising their governments, the correlations between Ethnology and Anthropology, the various schools in Anthropology and the relationship between social and cultural Anthropologies, and other relevant issues concerning global and Vietnamese Anthropology today. Prof Susan Bayly is a Professor of Historical Anthropology, Director of Graduate Studies and Chair of the PhD Committee for the Division of Social Anthropology, University of Cambridge. Her research interests include the South Asian caste system. Her selected published works include: How to Forge a Creative Student-Citizen: Achieving the Positive in Today’s Vietnam Modern Asian Studies 48, no. 3: 493-523 (2014); ‘Mapping Time, Living Space: The Moral Cartography of Renovation in Late-Socialist Vietnam’, Cambridge Anthropology 31:2, pp. 60-84 (2013); ‘For Family, State and Nation: Achieving Cosmopolitan Modernity in Late-Socialist Vietnam’, in N. Long and Henrietta Moore, eds. The Social Life of Achievement: Berghahn (2013); Anthologised versions of my ‘French anthropology and the Durkheimians in colonial Indochina’, Modern Asian Studies 34,3 July 2000, in a volume on French colonialism from Nebraska University Press, and in Engaging Colonial Knowledge (Palgrave), eds. R. Roque and K. Wagner (2012); ‘From History to Anthropology: Reflections on Caste from South India & Vietnam’, in D.S. Babu & R. S. Khare, eds., Caste in Life: Experiencing Inequalities (New Delhi: Pearson) (2010); ‘Hanoi intellectuals as contributors to the cultural life of the Vietnamese Revolution’, in Proceedings of the 3rd International Conference of Vietnamese Studies 2008, Hanoi. (in Vietnamese) (2010); Asian Voices in a Post-Colonial Age: Vietnam, India and Beyond. Cambridge University Press (2007); Caste, Society and Politics in India from the Eighteenth Century to the Modern Age. The New Cambridge History of India. Cambridge University Press (2001); Saints, Goddesses and Kings: Muslims and Christians in South Indian Society, 1700-1900. Cambridge University Press (1989).Tran Van Kham